Impact of Corporate Social Responsibility and Corporate Governance on Business Performance at PT Delitech Indojaya Lestari Medan - Ali Syah Putra; Benny Lim; Jung Sen; Ester; Javerson Simamora (Jurnal Kolaboratif Sains, 2024)
Corporate social responsibility has become integrated into business practices now as firms need corporates social responsibility if they want to keep up with the competition around them. The implementation of corporate social responsibility policies could then be argued to be a give and take act, where firms need to give something to society around them if they wanted to be able to take the benefits that are associated with them. The development of business competition today is very sharp and complex, therefore the management of a company must have a better strategy in a more complete, faster way so that management can make decisions quickly and accurately. In achieving company goals and attracting consumer buying interest to use production from the company, companies need to hold various promotional policies that are considered to support the sale of these products. In order to generate a sustainable profit, companies have to first complete their basic obligations which is obligations towards the stakeholders. This is because generating sustainable profit is only possible when a good corporate image is built. It makes companies more accountable and transparent to investors and gives them the tools to respond to stakeholder concerns. Corporate governance also contributes to development by helping facilitate new investment, access to capital, and long-term sustainability for firms, leading to economic growth and increased employment opportunities across markets. Corporate governance frameworks benefit firms through greater access to financing, lower cost of capital, better performance and more favorable treatment of all stakeholders. Regression analysis is used to perform regression on the relationships between the variable so as to understand the relationship between variable. In the regression model, corporate social responsibility and corporate governance are determined to predict business performance in equation Y= 3.568 + 0.380 X1 + 0.294X2. These results describes that a unit increase in corporate social responsibility has impact for maintaining business performance in amount of 0.379 unit and a unit increase in corporate social responsibility has impact for maintaining business performance in amount of 0.294 unit. In Z test, the Z count is 8.46. The alternative hypothesis is accepted and null hypothesis is rejected because Z count (8.46) is higher than Z table (1.96). This means that the corporate social responsibility has significant impact on business performance in PT Delitech Indojaya Lestari. It can be concluded from z test that the corporate social responsibility will significantly explain business performance. In Z test, the Z count is 8.45. The alternative hypothesis is accepted and null hypothesis is rejected because Z count (8.45) is higher than Z table (1.96). This means that the corporate governance has significant impact on business performance in PT Delitech Indojaya Lestari. It can be concluded from z test that the corporate governance will significantly explain business performance.